The teaching/learning of pronouns through the first year middle school textbook, between method and support. - Hamamdia, Samir (Milev Journal of Research and Studies, 2023)
This paper tackles the teaching of pronouns to first year pupils of the middle school through the textbook. It initially aims to check whether the authors of this book really implement the inductive method in teaching grammar using suggested texts. It investigates whether these texts guarrentee an inductive teaching of grammar in an effective way that enables first year pupils to master the use of some French pronouns.